1996
DOI: 10.1111/j.1540-8159.1996.tb03156.x
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Risk for Interaction Between Mobile Phones and Single Lead VDD Pacemakers?

Abstract: Mobile phones may cause pacemaker interference. Patients with a single lead VDD pacemaker might be at special risk, since the atrial sensitivity is often programmed to low (high sensitivity) threshold values and the majority of patients are pacemaker dependent due to the underlying high degree AV block. We evaluated 31 patients with three types of single lead VDD pacemakers: 12 Unity, 292-07 (Intermedics, Inc.); 10 Thera VDD, 8948 or 8968i (Medtronic, Inc.); and 9 Saphir 600 (Vitatron, Inc.) for interference f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 1 publication
0
15
0
Order By: Relevance
“…New generation of pacemakers are reported to be more protected against electromagnetic field due to the fact that they are equipped with more developed perception filters [9,[24][25][26][27]. In the new pacemaker models by the same manufacturer, there are specific perception filters and smaller battery sizes which all reduce the risk of being adversely affected by the magnetic field to a significant degree [16,28,29]. Hayes et al [21] emphasized the fact that the risk of being affected was related to the model of the pacemaker rather than its brand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…New generation of pacemakers are reported to be more protected against electromagnetic field due to the fact that they are equipped with more developed perception filters [9,[24][25][26][27]. In the new pacemaker models by the same manufacturer, there are specific perception filters and smaller battery sizes which all reduce the risk of being adversely affected by the magnetic field to a significant degree [16,28,29]. Hayes et al [21] emphasized the fact that the risk of being affected was related to the model of the pacemaker rather than its brand.…”
Section: Discussionmentioning
confidence: 99%
“…The mode of the pacemaker, its lead polarity and sensitivity, the output power and the antenna length of the mobile phone and the distance between the mobile phone and the pacemaker have all been reported to be influential on the adverse effects of the mobile phones on pacemakers [9][10][11]. There are in vitro [10,[12][13][14] and clinical studies [9,[15][16][17][18] reporting that Global System for Mobile Communication (GSM) mobile phones operating with digital technology might have adverse effects on pacemaker functions. Yet, the question of whether the use of mobile phones is safe for patients with pacemakers remains unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, concerns have been raised about the interference produced by mobile devices such as analogue/digital phones and hand-held radios. PMs are designed to work with bandlimited signals up to few hundred hertz; nevertheless, several authors have shown adverse effects from devices working at 900 MHz (Barbaro et al 1995, Hayes 1996, Carillo et al 1995, Irnich et al 1996, Barbaro et al 1996, Nowak et al 1996, Sparks et al 1996, Wilke et al 1996. Scarce attention has been paid to the mechanisms behind these interferences.…”
Section: Discussionmentioning
confidence: 99%
“…The topic of electromagnetic interference (EMI) between mobile phones and pacemakers (PMs) has raised much interest among physicists since 1994, when several sets of research data were reported on the adverse effects of electromagnetic fields radiated from mobile phones on implantable PMs (Barbaro et al 1995, 1996, Hayes 1996, Carillo et al 1995, Irnich et al 1996, Nowak et al 1996, Sparks et al 1996.…”
Section: Introductionmentioning
confidence: 99%
“…Mobile communication systems have gained great diffusion in the last decades, but their potential electromagnetic interference (EMI) with medical devices, especially electrical implantable devices, has raised no little concern. So far, several studies have investigated both in vivo and in vitro the potential adverse effects of mobile terminals on PM and implantable cardioverters 4–10 . New filtering techniques and components were included to minimize the effects observed in early PMs 11–13 …”
Section: Introductionmentioning
confidence: 99%